Thermal pollution zones on the aquatic environment from the coastal power plant: Numerical study - Alibek Issakhov; Yeldos Zhandaulet (Case Studies in Thermal Engineering, 2021)
In this work the results of a numerical study of thermal pollution from the power plant operation using the Irtysh River as a natural water cooling system have been presented. In the paper, a 2D model has been used to numerically simulate a floating stream along with its mixing heated water discharge characteristics from lateral projections with a transverse flow. The values of computational modeling are in good adjustment with the measurement results, in particular, with the trajectories of the jets, the recirculation zone size and the distribution of the dimensionless excess temperature. The work was also conducted to study thermal pollution in various scenarios of the heated water discharge from the coastal power plant and thermal pollution areas were determined for various discharge speed cases. The general projections of the thermal pollutant transfers in the river during the placement of the discharge channels, both for short and for long distances from the city were evaluated. It could be noted that using several discharge channels leads to a reduction in the area of thermal pollution. So for the discrepancy in temperature value from the water temperature of 3 °C there was a reduction in the pollution area of almost 11 times.